Why do I listen to this? Voices from university students using websites to practice listening comprehension - Rizaldy Hanifa; Siti Rahimah Yusra (Studies in English Language and Education, 2024)
Technological advancements in the 4.0 era have made it possible for English language learners to access online resources at any moment in any place, including websites that provide learners with a wider variety of auditory inputs. Despite this, some students may find it difficult to navigate independently owing to the vast quantity of websites. This research aims to discover the websites utilized by English major students at a state university in West Sumatra in independent listening practices, as well as their underlying motivations for selecting those websites. Using a qualitative case study, the data were collected using a questionnaire that was administered to 105 fifth-semester university students, and presented according to the frequency. The findings recorded a total of 34 websites used by students for practicing listening to enhance proficiency in deciphering unfamiliar words, acquiring knowledge of English sounds, and comprehending spoken utterances. The students further confirmed that materials found through the sources provided them with a sense of ease in learning. These initiatives demonstrated the students proficiency in utilizing technology for additional learning inputs. Nevertheless, the effectiveness of these learning modes still needs to be confirmed as the duration spent by learners may not be sufficient. Further research is recommended to analyze the websites selected by students to provide more tangible evidence regarding the suitability of the material for learning.